ANALISIS PENGGUNAAN MEDIA WORDWALL BERBASIS TPACK PADA MATA PELAJARAN IPAS SISWA KELAS IV SEKOLAH DASAR - Listyoningrum, Yuni; Rochana, Tatin; Zulfiati, Heri Maria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to see and determine the uses and benefits of TPACK-based Wordwall media in the science and science subject for class IV students at SDN 1 Kaloran, Temanggung Regency. The method in this research is descriptive qualitative. The variable in this research is the use of Wordwall media (single variable). The research subjects were 42 male and female class IV students as well as two class IV homeroom teachers. Research data was obtained based on interviews and observations. Data analysis techniques are data reduction, data display, and verification. The results of this research are that there are significant benefits in using TPACK-based Wordwall media in science subjects, especially in local regional wisdom. The conclusion of this research is that wordwall media is an interactive and effective media, using it makes students think more critically and students are not afraid of making mistakes, answering questions are more relaxed and not burdened because the questions are game-based with writing assignments. Apart from being easy and cheap to use, using this media requires a stable network condition and the ability to operate laptops and other devices well.